The Effect of Leverage and Tunneling Incentives on Transfer Pricing: A Study on Consumer Goods Industry Listed on Indonesia Stock Exchange - Sari Nuzullina Rahmadhani; Rana Fathinah Ananda (Universitas Padjadjaran, 2022)
This study examines the effect of leverage and tunnelling incentive on the company's decision to transfer pricing in consumer goods industry sector companies listed on the Indonesia Stock Exchange in 2015-2020. The technique used in sampling is purposive sampling, with a sample of 15 consumer goods industry companies. The data used in this study is secondary data in companies' financial reports. The analysis model used in this study is multiple linear regression with a significant level of 5%. The analysis results showed that leverage measured by debt to equity ratio has a significant positive effect on transfer pricing, tunnelling incentive measured by ownership share above 20% has a significant positive impact on transfer pricing